The Antecedents of Impulse Buying Behavior During Covid-19 Pandemic: Revealing the Role of Panic Buying, Government Stimulus, Perceived Scarcity, and Fear Appeals - Alfian Budi Primanto; Rahmawati Rahmawati (Universitas Airlangga, 2021)
COVID-19 pandemic spread around the world and changed people's shopping habits. This phenomenon causes much fear and induces panic behavior. In a highly uncertain situation, many people are more likely to engage in impulse buying behavior during this period. Our research aims to examine that impulse buying behavior during the pandemic. Hypothesis testing in this study uses the path analysis technique, which is processed using a computer with a program that has been developed by Preacher-Hayes, namely the Macros PROCESS technique. The research finds that panic buying, government stimulus, perceived scarcity, and fear appeal have a significant direct effect on impulse buying behavior. We went a step further to test the indirect effects. The indirect test supports our hypothesis by using fear appeal as mediating variable. The result indicates that fear appeal mediates between panic buying, whereas impulse buying behavior has no significant effect. Furthermore, fear appeal mediates between government stimulus, and scarcity of essential products has a significant effect on impulse buying behavior.